Incidence and patterns of violent and/or traumatic deaths between 1993 and 1999 in the Transkei region of South Africa - Meel, B L (The journal of trauma, 2004)
Incidence and patterns of violent and/or traumatic deaths among 4,525 victims over a 7-year period in the Transkei region of South Africa were investigated. Retrospective review and analysis was performed of all medicolegal autopsies (n = 6,181) between January 1993 and December 1999, of which 4,525 were violent or traumatic deaths. During the 7-year period (January 1993-December 1999), violent and/or traumatic deaths in the Transkei region accounted for an average annual rate of 162 per 100,000 of the population. The common causes of deaths per 100,000 of population per year were as follows: motor vehicle collisions, 63; firearm injuries, 43; stab wounds, 32; and blunt trauma, 24. Male subjects outnumbered female subjects by a 3.3:1 ratio. The murder rate in female subjects was 18 per 100,000 population. The murder rate in this area increased from 94 per 100,000 in 1993 to 121 in 1999. Nearly 50% of the violent and/or traumatic deaths occurred in the 21- to 40-year age group. There has been an increase in nontraumatic deaths such as hanging (1.5 times) and poisoning (5 times). The average annual incidence of violent and/or traumatic deaths in the Transkei region of South Africa is 162 per 100,000 population. Firearm-related deaths, at 43 per 100,000 of the population per year, have contributed substantially to this high incidence. This is a major cause of concern.